Activated neutrophils exert myeloid-derived suppressor cell activity damaging T cells beyond repair - Aarts, Cathelijn E. M. (Blood Adv, 2019)
Myeloid-derived suppressor cells (MDSCs) have the capacity to suppress T-cell–mediated immune responses and impact the clinical outcome of cancer, infections, and transplantation settings. Although MDSCs were initially described as bone marrow–derived immature myeloid cells (either monocytic or granulocytic MDSCs), mature neutrophils have been shown to exert MDSC activity toward T cells in ways that remain unclear. In this study, we demonstrated that human neutrophils from both healthy donors and cancer patients do not exert MDSC activity unless they are activated. By using neutrophils with genetically well-defined defects, we found that reactive oxygen species (ROS) and granule-derived constituents are required for MDSC activity after direct CD11b-dependent interactions between neutrophils and T cells. In addition to these cellular interactions, neutrophils are engaged in the uptake of pieces of T-cell membrane, a process called trogocytosis. Together, these interactions led to changes in T-cell morphology, mitochondrial dysfunction, and adenosine triphosphate depletion, as indicated by electron microscopy, mass spectrometry, and metabolic parameters. Our studies characterize the different steps by which activated mature neutrophils induce functional T-cell nonresponsiveness and irreparable cell damage.